2018
DOI: 10.5603/gp.a2018.0007
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic symptoms of the Couvade syndrome in Finnish and Polish expectant fathers

Abstract: Objectives: The aim of the study was to assess the occurrence of symptoms associated with the Couvade syndrome in two groups of men of Polish and Finnish nationality, and to perform a comparative analysis. Material and methods:The study was conducted in two groups of men (expectant fathers): 51 Poles and 40 Finns using a self-constructed questionnaire prepared in Polish and English languages. The statistical analysis was performed in Microsoft Office Excel 2010 and Statistica 12. The Pearson's test was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…On the other hand, Ganapathy T. in his study observed the occurrence of Couvade Syndrome in 77% of the partners of pregnant women [2]. Sioma-Markowska, Zyg and Kielbratowska in their work proved that as many as 98% of the respondents suffer from this syndrome [9]. However, in the available literature related to Couvade Syndrome in men, there is no information on its incidence with consideration of diseases complicating the current pregnancy of their female partners.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…On the other hand, Ganapathy T. in his study observed the occurrence of Couvade Syndrome in 77% of the partners of pregnant women [2]. Sioma-Markowska, Zyg and Kielbratowska in their work proved that as many as 98% of the respondents suffer from this syndrome [9]. However, in the available literature related to Couvade Syndrome in men, there is no information on its incidence with consideration of diseases complicating the current pregnancy of their female partners.…”
Section: Discussionmentioning
confidence: 97%
“…The present study also showed that those men, who had a low level of involvement in their partner's current pregnancy (37.5%), were less likely to observe the occurrence of symptoms of Couvade Syndrome. Sioma-Markowska, Zyg and Kielbratowska observed an identical relationship -men, who showed high involvement in pregnancy, were more likely to develop Couvade Syndrome than those who were involved to a lower extent [9].…”
Section: Syndrom Kuwady Wśród Partnerów Kobiet W Ciąży Fizjologicznej...mentioning
confidence: 88%
See 3 more Smart Citations